Dynamic capabilities for digital transformation. Issue 2 (20th September 2021) - Ellström, Daniel; Holtström, Johan; Berg, Emma; Josefsson, Cecilia
Abstract : Purpose: The purpose of this paper is to identify sensing, seizing and reconfiguring routines of dynamic capabilities that enable digital transformation in firms. Design/methodology/approach: A qualitative approach is used. Representatives from a firm going through digital transformations are interviewed, and focus groups have been carried out with a consultancy firm experienced in giving advice to firms going through digital transformation. Findings: Six routines identified as relevant specifically for digital transformation are identified. These are cross-industrial digital sensing, inside-out digital infrastructure sensing, digital strategy development, determination of enterprise boundaries, decomposition of digital transformation into specified projects and creation of a unified digital infrastructure. Practical implications: The authors provide direction for managers on how to approach digital transformation. In relation to previous research, the authors provide more specific guidance regarding how to reconfigure the organization in digital transformation. Originality/value: The paper uses a novel context for digital transformation and complements the very few studies available using dynamic capabilities to understand digital transformation.